Yohanes Calvin: Politik, Jabatan Gerejawi, dan Relevansinya bagi Gereja Masa Kini - Mery Kolimon (Jurnal Ledalero, 2016)
Recalling the Reformation movement of five hundred years ago provides us, the Churches throughout the world, with an opportunity to undertake a critical reflection on the meaning of the Reformation for us. In the Indonesian context, in particular relating to the relationship between Church and State, and the function of the Church in politics, we can learn from the legacy of John Calvin. This Reformation figure underlined the importance of separating the function of Church officials from that of State officials. Church pastors/ shepherds are responsible for taking care of the spiritual needs and the education of God’s people so that they can participate in politics as a faith responsibility. This is a duty that needs to be carried out with full commitment. Meanwhile the government and politicians work for the wellbeing of the people in the civic and governance spheres. Church and State have their own particular spheres of operation that should never be confused. Keywords: John Calvin, the reforms, ecclesiastical office, a Protestant church, politics, Indonesia ------------------------------------------------------------------------------------------------------------------------ Memperingati lima ratus tahun gerakan Reformasi memberikan kepada kita, Gereja-gereja di seluruh dunia, kesempatan untuk melakukan refleksi kritis atas makna Reformasi bagi kita. Dalam konteks Indonesia, khususnya berkaitan dengan hubungan antara Gereja dan Negara, dan fungsi Gereja dalam politik, kita bisa belajar dari warisan Yohanes Calvin. Reformasi ini menggarisbawahi pentingnya pemisahan fungsi jabatan Gereja dari jabatan Negara. Para gembala bertanggung jawab mengurusi kebutuhan spiritual dan pendidikan umat Allah sehingga mereka dapat berpartisipasi dalam politik sebagai tanggung jawab iman. Ini adalah tugas yang perlu dilakukan dengan komitmen penuh. Sementara itu, pemerintah dan politisi bekerja untuk kesejahteraan rakyat di bidang sipil dan pemerintahan. Gereja dan Negara masing-masing memiliki bidang khusus yang tidak boleh saling berebutan satu sama lain. Kata-kata kunci: Yohanes Calvin, reformasi, jabatan gerejawi, gereja Protestan, politik, Indonesia